2015
DOI: 10.1111/brv.12207
|View full text |Cite
|
Sign up to set email alerts
|

A synthesis of two decades of research documenting the effects of noise on wildlife

Abstract: Global increases in environmental noise levels - arising from expansion of human populations, transportation networks, and resource extraction - have catalysed a recent surge of research into the effects of noise on wildlife. Synthesising a coherent understanding of the biological consequences of noise from this literature is challenging. Taxonomic groups vary in auditory capabilities. A wide range of noise sources and exposure levels occur, and many kinds of biological responses have been observed, ranging fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
573
2
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 609 publications
(638 citation statements)
references
References 277 publications
13
573
2
2
Order By: Relevance
“…International legislation, such as the US National Environmental Policy Act and the European Commission Marine Strategy Framework Directive, recognizes the need to assess and manage the biological impacts of human‐generated noise (Slabbekoorn et al., 2010). Recent studies have demonstrated that human‐generated sound can detrimentally affect animal hearing, communication, movements, and foraging (Shannon et al., 2015; Slabbekoorn et al., 2010). However, it is difficult to translate these effects into meaningful predictions about individual fitness and population‐level consequences, (Morley, Jones, & Radford, 2014) because animals could possibly move away from sound sources, the disturbance may be transient and the animals could compensate to prevent long‐term impacts (Bejder et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…International legislation, such as the US National Environmental Policy Act and the European Commission Marine Strategy Framework Directive, recognizes the need to assess and manage the biological impacts of human‐generated noise (Slabbekoorn et al., 2010). Recent studies have demonstrated that human‐generated sound can detrimentally affect animal hearing, communication, movements, and foraging (Shannon et al., 2015; Slabbekoorn et al., 2010). However, it is difficult to translate these effects into meaningful predictions about individual fitness and population‐level consequences, (Morley, Jones, & Radford, 2014) because animals could possibly move away from sound sources, the disturbance may be transient and the animals could compensate to prevent long‐term impacts (Bejder et al., 2006).…”
Section: Introductionmentioning
confidence: 99%
“…A wealth of literature exists on the benefits of tranquillity, amongst which qualities of particularly sound, have gained increasing political attention and subsequently academic interest in the US since the 1980s (Miller, 2008;Shannon et al, 2015) and in Europe, especially since 2000 (e.g., Gidlöf-Gunnarsson &Öhrström, 2007;Watts & Pheasant, 2015). Much of this research has taken the traditional, directional questioning approach in consulting with the public on landscape qualities and particularly so on noise factors.…”
Section: Introductionmentioning
confidence: 99%
“…At present, available data are insufficient to accurately assess the long-term impacts of marine organisms exposed to chronically elevated noise levels (Parsons et al 2009, Kight & Swaddle 2011, Ellison et al 2012, Hawkins et al 2015, Shannon et al 2015, de Soto 2016. In addition, the recognition of anthropogenic noise as a stressor for marine mammals (Southall et al 2007, Hildebrand 2009, Ellison et al 2012) and the concerns for synergistic cumulative impacts from multiple stressors on the Gulf of Mexico marine ecosystem warrant continued noise monitoring and impact assessments.…”
Section: Discussionmentioning
confidence: 99%